Total recovery from monoclonal gammopathy and autoimmune phenomena after parathyroidectomy (2012)
Based on the observation of a patient with a causal relationship between hyperparathyroidism and development of both autoimmune disease and paraproteinemia, we hypothesize a novel cause of autoimmunity triggered in the context of hyperparathyroidism. © Cañas et al.; Licensee Bentham Open.